2020
DOI: 10.1021/acsinfecdis.0c00384
|View full text |Cite
|
Sign up to set email alerts
|

Periplasmic Targets for the Development of Effective Antimicrobials against Gram-Negative Bacteria

Abstract: Antibiotic resistance has emerged as a serious threat to global public health in recent years. Lack of novel antimicrobials, especially new classes of compounds, further aggravates the situation. For Gram-negative bacteria, their double layered cell envelope and an array of efflux pumps act as formidable barriers for antimicrobials to penetrate. While cytoplasmic targets are hard to reach, proteins in the periplasm are clearly more accessible, as the drug only needs to breach the outer membrane. In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 180 publications
(427 reference statements)
0
25
0
Order By: Relevance
“…Previous studies have reported that acrA serves as a bridge between the multidrug efflux pump subunit AcrB (acrB, linked inner membrane) and the outer membrane protein TolC (tolC, linked outer membrane) in the periplasmic region. Thus, the lower abundance of acrA proteins in the OS supernatant might be due to interactions that mediate acrB‐acrA‐tolC assembly [27]. Although acrA protein is known as periplasmic protein, we conclude that they cannot be enriched by OS lysis, as they possess characteristics that structurally couple them to membranes.…”
Section: Figurementioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies have reported that acrA serves as a bridge between the multidrug efflux pump subunit AcrB (acrB, linked inner membrane) and the outer membrane protein TolC (tolC, linked outer membrane) in the periplasmic region. Thus, the lower abundance of acrA proteins in the OS supernatant might be due to interactions that mediate acrB‐acrA‐tolC assembly [27]. Although acrA protein is known as periplasmic protein, we conclude that they cannot be enriched by OS lysis, as they possess characteristics that structurally couple them to membranes.…”
Section: Figurementioning
confidence: 90%
“…However, the data from OS lysis indicates that periplasmic proteins are relatively more enriched to the lysate in the supernatant, while membrane proteins in the pellet fraction: these results are consistent with other data on cellular localization (e.g., UniProt database). Examples of periplasmic proteins include the thiol:disulfide interchange protein DsbA (dsbA), the outer membrane lipoprotein carrier protein (lolA), the maltose/maltodextrin‐binding periplasmic protein (malE), the chaperone SurA (surA), the high‐affinity zinc uptake system protein ZnuA (znuA), and the tol‐Pal system protein TolB (tolB) [24,27]; in the bottom‐up analyses, these proteins were found to be more abundant in the OS supernatant fraction, as expected. However, the multidrug efflux pump subunit AcrA (acrA), reported as a periplasmic protein, was more abundant in the OS pellet fraction.…”
Section: Figurementioning
confidence: 99%
“…The periplasm is a unique feature of Gram-negative bacteria and houses a rich collection of small molecule ions, proteins, glucans, and the peptidoglycan scaffold. These components play important roles in structural support, cell division, secretion, envelope stress responding, signaling, and mobility [16][17][18][19]. The peptidoglycan scaffold (about 1.5-10 nm) in Gram-negative bacteria normally contains one or two layers of the interconnected structure, which is about one-tenth the thickness of the cell wall in Gram-positive bacteria (about 20-80 nm) [20].…”
Section: Figurementioning
confidence: 99%
“…Before adopting their functional states in the OM, OMP precursors must first traverse the hydrophobic inner membrane and then pass through the aqueous periplasmic space before being properly inserted into the OM and folding correctly ( 3 ). Understanding the biogenesis of OMPs enables the design of new antibiotics that interfere with these processes ( 4 ), thus providing new strategies for combating various pathogenic bacteria, such as Pseudomonas aeruginosa and Salmonella enterica .…”
Section: Introductionmentioning
confidence: 99%